Epidemiology of birth defects in a national hospital-based birth defect surveillance spot in Southern Jiangsu, China, 2014–2018 - Zhou, Ying; Yang, Di; Mao, Xueqin; Zhou, Hua; Wang, Li (Frontiers in Medicine, 2023)
Objective: As the only hospital-based national surveillance spot of birth defects (BDs) in Changzhou city located in the economically developed eastern part of China, Changzhou Maternal and Child Health Care Hospital has encountered serious challenges in BDs prevention. This study aimed to describe the epidemiology of total BDs born in the hospital from 2014 to 2018. Methods: The data were collected from the national hospital-based birth defect surveillance system. BD prevalence was calculated by Poisson distribution. Trends of prevalence and the associations of regarding information with BDs were analyzed by Poisson regression. Results: The reported prevalence of total BDs was 313.92 (95% confidence interval [CI]: 299.59–328.76) per 10000 perinatal infants (PIs), while the perinatal prevalence of BD was 160.19 (95% CI: 150.00–170.89) per 10000 PIs. A remarkable uptrend in the prevalence of BDs was noticed with a prevalence rate ratio (PRR) of 1.09 (95% CI: 1.04–1.14) and 1.13 (95% CI: 1.09–1.16), respectively. Congenital heart disease (CHD), cleft lip with or without cleft palate (CL/P), congenital malformation of the kidney (CMK), polydactyly, Down syndrome (DS), cystic hygroma, neural tube defect (NTD), and congenital talipes equinovarus (CTE) were common types of total BDs. Mothers living in the urban area (PRR = 1.67, 95% CI:1.50-1.87), male fetuses (PRR = 1.16, 95% CI: 1.05-1.28), and maternal age under 20 (PRR = 2.28, 95% CI: 1.60-3.25) and 25 (PRR = 1.41, 95% CI: 1.22-1.63) or over 35 (PRR = 1.18, 95% CI: 1.00-1.40) years were risk factors for BD occurrence. Conclusion: The reported prevalence of total BDs was nearly two times higher than perinatal prevalence of BDs in PIs, and the ranks of total BDs and BDs in PIs were different. Mothers living in the urban area, male fetuses, and maternal age under 25 or over 35 years were risk factors for BD incidence. Thus, improving prenatal examination technology, expanding the surveillance time quantum of BDs, and keeping maternal healthy may be warranted.